Web-based high-intensity bodyweight interval training improves metabolic health and physical fitness outcomes in middle-aged men with obesity during the COVID-19 pandemic - Hwang, Dong-Joo; Choi, Dong-Hun; Hyun, Ah-Hyun (Frontiers in Physiology, 2025)
Reduced opportunities for physical activity during the COVID-19 pandemic have heightened obesity-related health risks, emphasizing the need for effective, scalable, and remotely deliverable exercise interventions. This randomized controlled trial examined the efficacy of an 8-week, real-time, supervised, web-based high-intensity interval training (HIIT) program in improving metabolic health and physical fitness in middle-aged men with obesity. Twenty-two men (age <45 years; BMI >30 kg/m2; waist circumference >90 cm) were assigned to a videoconference-based HIIT intervention or a non-exercise control group. The HIIT group completed two supervised sessions per week, each consisting of a standardized warm-up, a 20-min HIIT protocol, and a cool-down, with real-time monitoring and weekly dietary log reviews. Web-based HIIT significantly reduced fat mass by 6.6% (−2.01 kg; d = 1.38) without altering total body weight and improved lipid profiles by increasing HDL cholesterol and decreasing total and LDL cholesterol. Leptin levels decreased, adiponectin increased, and IL-10 rose, whereas IL-6 remained unchanged. Cardiorespiratory fitness improved, with VO2max increasing by 3.06 mL·kg-1·min-1 (∼8.7%) and minute ventilation increasing, and muscle performance was enhanced, as trunk extensor peak torque and average power increased by 9.7% and 30.2%, respectively, and knee flexor peak torque increased by 31.8% (right) and 19.5% (left), yielding large effect sizes (d = 0.9–1.3). These findings indicate that real-time, non-face-to-face HIIT effectively enhances body composition, lipid metabolism, inflammatory balance, aerobic capacity, and functional muscle performance in men with obesity, supporting this contactless modality as a feasible and deployable strategy for health maintenance during and beyond pandemic-related restrictions.